Quark-parton phase transitions and the entropy problem in quantum mechanics - Kim, Y.S. (Вопросы атомной науки и техники, 2001)
Since Feynman proposed his parton model in 1969, one of the most pressing problems in high-energy physics has been whether partons are quarks. It is shown that the quark model and the parton model are two different manifestations of one covariant entity. The nature of transition from the confined quarks to plasma-like partons is studied in terms of the entropy and temperature coming from the time-separation variable. According to Einstein, the time-separation variable exists wherever there is a spatial separation, but it is not observed in the present form of quantum mechanics. The failure to observe this variable causes an increase in entropy.